2009
DOI: 10.1002/bem.20557
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exposure to 50 Hz magnetic field with or without insulin on blood–brain barrier permeability in streptozotocin‐induced diabetic rats

Abstract: We investigated the effect of long-term exposure to modulation magnetic field (MF), insulin, and their combination on blood-brain barrier (BBB) permeability in a diabetic rat model. Fifty-three rats were randomly assigned to one of six groups: sham, exposed to no MF; MF, exposed to MF; diabetes mellitus (DM), DM induced with streptozotocin (STZ); DM plus MF (DMMF); DM plus insulin therapy (DMI); and DM plus insulin therapy plus MF (DMIMF). All the rats underwent Evans blue (EB) measurement to evaluate the BBB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…Rats were exposed to a MF with 5.0 mT intensity and 50 Hz frequency in a special Plexiglas cage (40 × 17 × 13 cm) (19). The MF was generated in a specially designed device that had a solenoid 500 mm in length and 210 mm in diameter.…”
Section: Magnetic Field Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…Rats were exposed to a MF with 5.0 mT intensity and 50 Hz frequency in a special Plexiglas cage (40 × 17 × 13 cm) (19). The MF was generated in a specially designed device that had a solenoid 500 mm in length and 210 mm in diameter.…”
Section: Magnetic Field Exposurementioning
confidence: 99%
“…The MF was generated in a specially designed device that had a solenoid 500 mm in length and 210 mm in diameter. This magnet was constructed by winding 1400 turns of an insulated soft copper wire, which was 1.4 mm in diameter, on a fiber base (19,20). A MF intensity of B = 5 mT was measured inside the solenoid using a digital teslameter (Phywe, Gottingen, Germany) with an axial Hall probe (Phywe).…”
Section: Magnetic Field Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…No effect was found in normoglycemic rats, leading to the conclusion that diabetes appears to increase the vulnerability of the BBB to the effects of ELF EMFs. Another study of the effects of diabetes upon magnetic field (MF)-induced BBB permeability (Gulturk et al 2010) revealed that long-term (30 days) exposure to MF increased the extravasation of Evans Blue through the BBB in normal rats, as well as diabetic rats both with and without insulin therapy. It was concluded that both untreated diabetes and MF exposure increased the BBB permeability, that there was a synergistic effect, and that insulin therapy decreased the effect.…”
Section: Introductionmentioning
confidence: 99%
“…26 It is also suggested that the exposure of 50 Hz ELF-MFs can cause oxidative stress-based nervous system pathologies associated with ageing 27 and increase blood brain barrier permeability. 28 Marchionni et al has reported that 50/60 Hz magnetic field can modify the firing rate of rat sensory neurons. 29 It has been shown that the cholinergic activity in the frontal cortex and hippocampus of the rat decreases immediately after exposure to 60 Hz magnetic field with different intensities 30 and 50 Hz ELF-EMF exposure can increase in vivo neurogenesis.…”
Section: Introductionmentioning
confidence: 99%